2014
DOI: 10.1097/med.0000000000000086
|View full text |Cite
|
Sign up to set email alerts
|

Testosterone and weight loss

Abstract: Purpose of reviewThe purpose of this article is to examine the contemporary data linking testosterone therapy in overweight and obese men with testosterone deficiency to increased lean body mass, decreased fat mass, improvement in overall body composition and sustained weight loss. This is of paramount importance because testosterone therapy in obese men with testosterone deficiency represents a novel and a timely therapeutic strategy for managing obesity in men with testosterone deficiency.Recent findingsLong… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
64
1
8

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(77 citation statements)
references
References 122 publications
(198 reference statements)
4
64
1
8
Order By: Relevance
“…It is universally accepted that T therapy in men with TD increases muscle mass and reduces fat mass (Table 2) [49]. T therapy improves bone mineral density [5051], reduces adipogenesis [5253] and improves anthropometric parameters (Tables 1 and 2) [8].…”
Section: Benefits Of T Therapy In Men With Tdmentioning
confidence: 99%
“…It is universally accepted that T therapy in men with TD increases muscle mass and reduces fat mass (Table 2) [49]. T therapy improves bone mineral density [5051], reduces adipogenesis [5253] and improves anthropometric parameters (Tables 1 and 2) [8].…”
Section: Benefits Of T Therapy In Men With Tdmentioning
confidence: 99%
“…T2DM is associated with augmented E 2 levels in men (123,124). These increased E 2 levels are associated with complications, such as atherosclerosis, in men with T2DM and metabolic syndrome (35,65).…”
Section: Effect Of Type 2 Diabetes On Androgen and Estrogen Levelsmentioning
confidence: 98%
“…Testosterone replacement therapy (TRT) in men with T2DM improved some of the key parameters associated with metabolic syndrome in several observational, retrospective, and prospective trials (38,55,79,119). In particular, body weight, waist circumference, blood pressure, heart rate, fasting blood glucose and insulin sensitivity, as well as HbA 1c , triglycerides, cholesterol, and low-density lipoprotein levels were significantly improved in type 2 diabetic men receiving TRT for at least 24 mo (34,123,141). In concordance, TRT in nine men with T1DM, erectile dysfunction, and hypogonadism improved in glycemic control, lipid profiles, and erectile function (104).…”
Section: Childhoodmentioning
confidence: 98%
“…Moreover, weight loss has also been demonstrated in controlled studies of shorter duration. Markers of metabolic and cardiovascular health are improved in hypogonadic men [96,97] but not in men without hypogonadism [98]. However, some studies have suggested that testosterone might increase cardiovascular risk, and although these have been strongly criticised, the FDA has decided to review the risks associated with testosterone treatment [97,99].…”
Section: Testosteronementioning
confidence: 99%